Education Level, Working Experiences and Ergonomics Training Effect on Ergonomics Awareness and Practices in Malaysia - Md Sirat, Rozlina; Mohd Rohani, Jafri; Ahmad, Norhayati; Mohamed Shaharoun, Awaluddin; Haron, Habibah (International Journal of Engineering and Technology, 2018)
The objective of the study is to identify the effect of three demographics factors: education level, working experiences and ergonomics training on ergonomics awareness (EA) and ergonomics practices (EP). 146 questionnaires were received from Safety and Health Officers (SHOs) in Malaysian manufacturing companies. Exploratory Factor Analysis has been carried out but not discussed in this paper. Ergonomics awareness (EA) represented by four elements: knowledge in ergonomics technical (KET), beliefs on implication of work and need for improvements (BIIWNI), beliefs on the importance of assessment (BIAss) and beliefs on the importance of anthropometrics and suitability to workers (BIASW). Ergonomics practices (EP) were represented by two elements; ergonomics technical (Ergo_Tech) and ergonomics administrative (Ergo_Ad). Analysis were carried out by Levene test, MANOVA, and linear regression (stepwise). It is found that ergonomics training and working experiences as SHO have significantly interact with EA, while only ergonomic training has significantly interacted with EP. Surprisingly, education level of SHOs did not contribute significantly to both EA and EP. It is concluded that ergonomics training should be emphasized in order to get a successful ergonomics practice and it should be considered as a compulsory in order to obtain continuous program (CEP) point for renewal of SHO certificate.Â